Parametric analysis of the influence of slat geometry on airframe noise by a commercial code - Bolivar, Laura Botero (2019)
Over recent years, airframe noise has become one of the most important research topics in the aeronautic field, due to reductions in engine noise with the development of high-bypass technology and the necessity to meet the new standards established by regulation entities. It is caused by fluid-structure interaction and pressure fluctuations caused by gaps and discontinuities. Slat is one of the major airframe noise sources due to the complex flow in the gap between it and the wing main element. Although some noise reduction techniques have been applied to the slat, the relation between the slat characteristics and the noise generation has not been completed understood. This study addresses 21 variations in six different parameters of the slat internal geometry for the establishment of their relation with noise generation. Modifications were focused on the cusp and trailing edge regions and their angle, length and thickness were varied. Comparisons between numerical and experimental results of some configurations validated the simulation methodology. Numerical studies were performed by PowerFLOW 5.3® commercial software and the results included transient analysis, as the far-field spectrum, turbulence in the slat cove, power spectra density contours in both flow around the slat and slat surface, and spectra of the pressure fluctuations on the slat surface, and stationary results as pressure coefficient distribution and lift and drag coefficients of the wing. On the other hand, experimental tests were conducted in a closed-section wind tunnel at the Laboratory of Aerodynamics (LAE) of the São Carlos School of Engineering and consisted in measurements of static pressure in the wall model through a ScaniValve and far-field noise through a phased array antenna of microphones, whose post-processing was completed by convectional and CLEAN SC beamforming methodologies. The good agreement in both aerodynamic and aerocoustic results proved the validity of the numerical set-up and the reliability of numerical results. Among all modified parts, the cusp length exerted the major influence on the slat noise and changed significantly the flow characteristics around the slat. However, the angle and thickness of the cusp showed no effect on the aerodynamic and aerocoustic properties of the wing. Some relationships were observed between the slat noise and characteristics of the fluid around the slat, which were constant among all slat modifications.